Ureteral Stents Harbor Complex Biofilms With Rich Microbiome-Metabolite Interactions. Issue 5 (1st May 2023) - Werneburg, Glenn T.; Hettel, Daniel; Lundy, Scott D.; Adler, Ava; De, Smita; Mukherjee, Sromona D.; Rackley, Raymond R.; Shoskes, Daniel A.; Miller, Aaron W.
Abstract : Purpose: We sought to determine microbe-metabolite composition and interactions within indwelling ureteral stent biofilms, determine their association with patient factors including infection, and reconstitute biofilm formation on relevant surface materials in vitro. Materials and Methods: Upon ureteral stent removal from patients, proximal and distal ends were swabbed. Samples were analyzed by 16S next-generation sequencing and metabolomics. A continuous-flow stir-tank bioreactor was used to reconstitute and quantify in vitro biofilm formation from stent-isolated bacteria on stent-related materials including silicone, polytetrafluoroethylene, polyurethane, polycarbonate, and titanium. Diversity, relative abundance, and association with clinical factors were analyzed with ANOVA and Bonferroni t -tests or PERMANOVA. Biofilm deposition by microbial strain and device material type were analyzed using plate counts and scanning electron microscopy following bioreactor incubation. Results: All 73 samples from 37 ureteral stents harbored microbiota. Specific genera were more abundant in samples from stents wherein there was antibiotic exposure during indwelling time ( Escherichia/Shigella, Pseudomonas, Staphylococcus, Ureaplasma ) and in those associated with infection ( Escherichia/Shigella, Ureaplasma ). The enriched interaction subnetwork in stent-associated infection included Ureaplasma and metabolite 9-methyl-7-bromoeudistomin. Strains identified as clinically relevant and central to interaction networks all reconstituted biofilm in vitro, with differential formation by strain ( Enterococcus faecalis most) and material type (titanium least). Conclusions: Ureteral stent biofilms exhibit patterns unique to stent-associated infection and antibiotic exposure during indwelling time. Microbes isolated from stents reconstituted biofilm formation in vitro. This work provides a platform to test novel materials, evaluate new coatings for anti-biofilm properties, and explore commensal strain use for bacterial interference against pathogens.